Zhongqiu Festival in Hwie Ing Kiong temple, Madiun - Anitia Octantiar Maunardani; C. Dewi Hartati (Fakultas Sastra Universitas Darma Persada, 2019)
Abstract. This paper discusses about one of Chinese festival, namely Moon Cake Festival. This festival is celebrated by Chinese people in Madiun, East Java in Hwie Ing Kiong temple. At Hwie Ing Kiong temple the Zhong Qiu festival is still held as a form of maintaining Chinese culture, and inherit to their future generation. Through the ritual id dedicated to Mazupo, the sea guardian deity as a main deity in this temple and also to the moon deity, Chinese people in Madiun maintain the existence of this festival. The ritual is held in night after that people enjoy the moon cake outside the temple. The festival still exist up to now because it is well acculturated with local culture.